The Bouguer Anomaly Map of Iraq According to a New Local Theoretical Gravity Equation and Its Geological Importance - Al-Banna, Ahmed S.; Al- Karadaghi, Salar S.; Abdullah, Hamed H. (Iraqi Journal of Science, 2020)
Four hundred and seventy eight gravity base stations in Iraq were used to obtain a new local theoretical gravity equation. The obtained equation was used to construct a Bouguer anomaly map of Iraq depending on the available gravity base stations. This map was compared with the Bouguer map constructed for the same stations using the international formula (1930). Good similarity in shapes and locations of the anomaly were observed, while the gravity anomaly values in the new map were increased by about 30 mGal. The eastern zero gravity contour line of the new obtained gravity map coincides with the western boundary of the tectonic Mesopotamian zone, while the main negative gravity values coincide with the Mesopotamian area, which contains most oil fields in eastern Iraq. All negative gravity anomaly areas coincide with the deepest basement rocks (the sedimentary basins) in Iraq. The obtained results are very valuable in geological applications.